2013
DOI: 10.2337/dc12-1040
|View full text |Cite
|
Sign up to set email alerts
|

Association of Glycation Gap With Mortality and Vascular Complications in Diabetes

Abstract: OBJECTIVEThe “glycation gap” (G-gap), an essentially unproven concept, is an empiric measure of disagreement between HbA1c and fructosamine, the two indirect estimates of glycemic control. Its association with demographic features and key clinical outcomes in individuals with diabetes is uncertain.RESEARCH DESIGN AND METHODSThe G-gap was calculated as the difference between measured HbA1c and a fructosamine-derived standardized predicted HbA1c in 3,182 individuals with diabetes. The G-gap’s associations with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 40 publications
3
33
0
2
Order By: Relevance
“…Hempe et al [18] and McCarter et al [21] have observed that a higher HGI level, calculated using self-glucose monitoring data to predict the value of HbA1c, is associated with a greater risk of developing nephropathy and retinopathy in patients with type 1 diabetes. Several studies have demonstrated a positive association between micro-and macrovascular complications of type 2 diabetes and glycation gap, an analogue measure of the discordance between the observed and the predicted levels of HbA1c, calculated as HGI except that fructosamine concentrations replace blood glucose levels in the formula used to calculate predicted HbA1c [34][35][36][37]. An increased HGI level, calculated using fasting plasma glucose concentration to predict HbA1c value, has been recently shown to identify a subgroup of the ACCORD population with a greater risk of diabetic complications, hypoglycemia and total mortality [22].…”
Section: Discussionmentioning
confidence: 99%
“…Hempe et al [18] and McCarter et al [21] have observed that a higher HGI level, calculated using self-glucose monitoring data to predict the value of HbA1c, is associated with a greater risk of developing nephropathy and retinopathy in patients with type 1 diabetes. Several studies have demonstrated a positive association between micro-and macrovascular complications of type 2 diabetes and glycation gap, an analogue measure of the discordance between the observed and the predicted levels of HbA1c, calculated as HGI except that fructosamine concentrations replace blood glucose levels in the formula used to calculate predicted HbA1c [34][35][36][37]. An increased HGI level, calculated using fasting plasma glucose concentration to predict HbA1c value, has been recently shown to identify a subgroup of the ACCORD population with a greater risk of diabetic complications, hypoglycemia and total mortality [22].…”
Section: Discussionmentioning
confidence: 99%
“…The glycation gap developed by Cohen et al ( 5 ) is calculated in exactly the same way as HGI except fructosamine replaces directly measured glucose for obtaining a predicted HbA 1c . Several studies have shown that patients with type 2 diabetes with a high glycation gap have greater risk for microvascular or macrovascular complications ( 5 , 10 , 13 , 14 ). HGI and the glycation gap are strongly positively correlated, which suggests they reflect the same biological phenomenon ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some medical investigators state these glycation gaps are associated with increased diabetic morbidity and mortality. 13 …”
Section: Hemoglobin A1c a Tired Overused Testmentioning
confidence: 99%